2001
DOI: 10.1016/s0014-5793(01)02581-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid functional analysis of protein–protein interactions by fluorescent C‐terminal labeling and single‐molecule imaging

Abstract: Detection of protein^protein interactions is a fundamental step to understanding gene function. Here we report a sensitive and rapid method for assaying protein^protein interactions at the single-molecule level. Protein molecules were synthesized in a cell-free translation system in the presence of Cy5-puro, a fluorescent puromycin, using mRNA without a stop codon. The interaction of proteins thus prepared was visualized using a single-molecule imaging technique. As a demonstration of this method, a motor prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…[100] Labeling is usually combined with multiple chromatography steps to purify the desired adducts. Alternative methods [101] are the native chemical ligation of recombinantly expressed and individually labeled protein fragments or intein-mediated protein splicing, [102] the specific reaction with thioester derivatives of dyes, [103] puromycin-based labeling using in-vitro translation, [104] and the introduction of non-natural amino acids. [105] Most of the latter methods are not yet used routinely and must be considered as under development.…”
Section: Protein Labelingmentioning
confidence: 99%
“…[100] Labeling is usually combined with multiple chromatography steps to purify the desired adducts. Alternative methods [101] are the native chemical ligation of recombinantly expressed and individually labeled protein fragments or intein-mediated protein splicing, [102] the specific reaction with thioester derivatives of dyes, [103] puromycin-based labeling using in-vitro translation, [104] and the introduction of non-natural amino acids. [105] Most of the latter methods are not yet used routinely and must be considered as under development.…”
Section: Protein Labelingmentioning
confidence: 99%
“…1B) was synthesized according to the published procedure (Yamaguchi et al 2001). Briefly, by the ordinary solid-phase phosphoramidite method, dC-CE-phosphoramidite and 5 0 -Amino-Modifier C6 (Glen Research, Sterling, VA) were coupled to puromycin, the N-amino group of which was protected with Nbenzyloxycarbonyl phenylalanine.…”
Section: Synthesis Of Fluorescent Puromycin Derivativementioning
confidence: 99%
“…Recent studies have revealed that in cell-free translation systems, lower concentrations of puromycin derivatives are preferentially incorporated into the Cterminus of proteins (Nemoto et al 1999). Using this method, various experiments including detection of protein-protein interaction (Yamaguchi et al 2001;Oyama et al 2006), protein-DNA interaction (Doi et al 2002) and protein expression in vivo (Starck et al 2004) have been reported. However, the yields of some labeled proteins are extremely low and there are few reports about this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Unwanted cysteine residues in the natural sequence are replaced with other amino acids by using site-directed mutagenesis, and new cysteines can be introduced at locations where they appear suitable for FRET studies and are likely to bind maleimide or haloacetamide derivatives of fluorescent dyes. Alternative methods also have been reported, [66][67][68][69][70] but they are currently not as widely used as the simple cysteine ligation. For FRET pair labeling, conditions are chosen such that equal amounts of donor and acceptor bind to the protein.…”
Section: Protein Labelingmentioning
confidence: 99%